2016
DOI: 10.1038/srep20115
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Actin Filament Dynamics during Mitosis in Wheat Protoplasts under UV-B Radiation

Abstract: Enhanced ultraviolet-B (UV-B) radiation is caused by the thinning ozone and affects photosynthesis and crop yield. Recently, UV-B radiation has been considered as an environmental signal that regulates plant growth. Elucidating the downstream effectors in UV-B-triggered pathways is of particular interest. Previous studies have shown that actin filaments (AFs) play many roles during cell physiological processes. However, the underlying response of AFs to UV-B radiation remains unclear. In this study, wheat prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…One of the many applications of the protoplasts technology is to establish a transient expression system which can be used to study high-throughput analysis and functional characterization of genes. To establish, efficient expression system through protoplasts there is requirement of high-quality protoplasts [24].…”
Section: Discussionmentioning
confidence: 99%
“…One of the many applications of the protoplasts technology is to establish a transient expression system which can be used to study high-throughput analysis and functional characterization of genes. To establish, efficient expression system through protoplasts there is requirement of high-quality protoplasts [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that UV-B promotes actin filament bundle formation in wheat protoplasts and induces abnormal chromosome movement [ 26 ]. Recently, it was reported that light was channeled through the stem to the roots [ 27 ], and UV-B signals could be transmitted to the roots through plant endodermis tissues [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In wheat protoplasts, UV-B irradiation disturbs the actin cytoskeleton, which forms foci at different stages of the cell cycle. Those effects are accompanied by the formation of apoptotic bodies (Chen and Han, 2016). UV-B-induced programmed cell death has also been reported for BY2 cells (Lytvyn et al, 2010).…”
Section: Discussionmentioning
confidence: 99%